Glutathione S-Transferase Pi Isoform (GSTP1) Expression in Murine Retina Increases with Developmental Maturity - Lee, Wen-Hsiang (2014)
BACKGROUND AND AIMS: Glutathione S-transferase pi isoform (GSTP1) is an intracellular detoxification enzyme that catalyzes reduction of chemically reactive electrophiles and is a zeaxanthin-binding protein in the human macula. We have previously demonstrated that GSTP1 levels are decreased in human age-related macular degeneration (AMD) retina compared to normal controls [1]. We also showed that GSTP1 levels parallel survival of human retinal pigment epithelial (RPE) cells exposed to UV light, and GSTP1 over-expression protects them against UV light damage [2]. In the present work, we determined the developmental time course of GSTP1 expression in murine retina and in response to light challenge. METHODS: Eyes from BALB/c mice at post-natal day 20, 1 month, and 2 months of age were prepared for retinal protein extraction and cryo sectioning, and GSTP1 levels in the retina were analyzed by Western blot and immunohistochemistry (IHC). Another group of BALB/c mice with the same age ranges was exposed to 1000 lux of white fluorescent light for 24 hours, and their retinas were analyzed for GSTP1 expression by Western blot and IHC in a similar manner. RESULTS: GSTP1 levels in the murine retina increased in ascending order from post-natal day 20, 1 month, and 2 months of age. Moreover, GSTP1 expression in murine retina at post-natal day 20, 1 month, and 2 months of age increased in response to brief light exposure compared to age-matched controls under normal condition. CONCLUSIONS: GSTP1 expression in retina increases with developmental age in mice and accompanies murine retinal maturation. Brief exposure to light induces GSTP1 expression in the murine retina across various developmental ages. GSTP1 induction may be a protective response to light-induced oxidative damage in the murine retina.